Problemas metodológicos en la investigación de las representaciones mentales referidas a temas biológico-naturalistas en los niños de la escuela primaria - Caravitas, S.; Tonucci, F. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
The aim of this paper is to deal with the methodological problems met by the researcher when studying aspects of the child's cognitive development in order to obtain helpful information to modify the school practice.